Combatting Salmonella: a focus on antimicrobial resistance and the need for effective vaccination - Junaid Nazir; Tasaduq Manzoor; Afnan Saleem; Ubaid Gani; Sahar Saleem Bhat; Shabir Khan; Zulfqarul Haq; Priyanka Jha; Syed Mudasir Ahmad (BMC Infectious Diseases)
Abstract Background Salmonella infections represent a major global public health concern due to their widespread zoonotic transmission, antimicrobial resistance, and associated morbidity and mortality. This review aimed to summarize the zoonotic nature of Salmonella, the challenges posed by antimicrobial resistance, the global burden of infections, and the need for effective vaccination strategies to mitigate the rising threat of Salmonella. Methods A systematic review of literature was conducted using databases such as PubMed, Scopus, Web of Science, and Google Scholar. Relevant studies published in English were identified using keywords including Salmonella, vaccination, antimicrobial resistance, and public health. Articles focusing on epidemiology, vaccine development, and strategies to control Salmonella infections were included, while conference abstracts and non-peer-reviewed studies were excluded. Results Salmonella infections result in approximately 95 million global cases annually, with an estimated 150,000 deaths. Regional variations were evident, with higher infection rates in low- and middle-income countries due to poor sanitation and food safety standards. Salmonella Enteritidis and S. Typhimurium were the most prevalent serovars associated with human infections. The review highlighted an alarming rise in multidrug-resistant (MDR) Salmonella strains, particularly due to the overuse of antibiotics in humans and livestock. Despite progress in vaccine development, challenges remain in achieving a universal vaccine that targets diverse Salmonella serovars. Live-attenuated, killed, recombinant, subunit, and conjugate vaccines are currently under development, but limitations such as efficacy, cost, and accessibility persist. Conclusions Salmonella infections continue to impose a significant burden on global health, exacerbated by rising antimicrobial resistance. There is an urgent need for a multifaceted approach, including improved sanitation, prudent antibiotic use, and the development of affordable, broad-spectrum vaccines. Strengthening surveillance systems and promoting collaborative global efforts are essential to effectively control and reduce the burden of Salmonella.